Effect of Trade Surplus on External Debt in Developing Countries: Evidence from General-to-Specific Model - Karia, Abdul Aziz; Hakim, Taufik Abd (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2026)
This paper examines the impact of trade openness towards external debt levels in low- and middle-income countries from 1980-2021. Using panel estimation of Fixed Effects (FE) and the General-to-Specific (GETS), the researchers segregated into Model 1 and Model 2, which Model 2 purposely to identify the interaction of international reserves as a potential medium to relate the impact of trade openness and external debt. The finding suggests that independent variables such as GDP growth rate, current account balance, and trade openness are highly significant variables that influence the external debt in the 50 LMICs. The researchers also found a robust interaction between trade openness and international reserves in determining external debt. The result confirms that the positive direct relationship of trade openness increases its coefficient from 0.10% to 0.14% after incorporating the interaction of international reserves in Model 2. The statistical evidence suggests that the inverse interactions of international reserves on trade openness significantly negatively affect external debt. Moreover, the result prevails, continuing to be positive and highly significant. Hence, the researchers can relate that an inverse impact of trade openness on international reserves has negatively affected external debt.